Decoupling Policy from Practice: The Case of Stock Repurchase Programs - Westphal, James D.; Zajac, Edward J. (Administrative Science Quarterly, 2001)
This study examines firms' decoupling of informal practices from formally adopted policies through analysis of the implementation of stock repurchase programs by large U.S. corporations in the late 1980s and early 1990s, when firms were experiencing external pressures to adopt policies that demonstrate corporate control over managerial behavior. We develop theory to explain variation in the responses of firms to such pressures, i.e., why some firms acquiesce by actually implementing stock repurchase programs, while others decouple formally adopted repurchase programs from actual corporate investments, so that the plans remain more symbolic than substantive. Results of a longitudinal study of stock repurchase programs over a six-year time period show that decoupling is more likely to occur when top executives have power over boards to avoid institutional pressures for change and when social structural or experiential factors enhance awareness among powerful actors of the potential for organizational decoupling. The study has implications for future research on decoupling, organizational learning, and corporate governance.